Problematika Pendidik dan Peserta Didik dalam Pembelajaran Pendidikan Agama Islam di MTs Pondok Pesantren Modern Darul Falah Kabupaten Enrekang - St Wardah Hanafie; Muhammad Siri Dangnga; Abdul Halik; Jabal Rahmah (Al-Ulum, 2019)
This article suggests the problematic of educators and students as learning actors so it is important to interact educative, conductively, effectively, and efficiently. Students as the next generation, it is important to be equipped with religious education (PAI) in order to have personality integrity. The success of students in PAI learning is influenced by creativity, commitment, dedication, and competence of educators implementing learning. It is important to examine the problem of educators and students in learning, the problem of learning Islamic education, and the solution to that problem. This research is Research and Development (R&D). The research findings in the field show among others: the problem of educators is the complexity of the character of students; limited learning time; mastery of subject matter; availability of learning tools; limited learning infrastructure; mastery of learning strategies and methods; participation in scientific training and meetings; and the density of activities at the cottage. The problem of students is also monotonous learning strategies and methods; high teaching material; memorization strategy; motivation to compete; and lack of discipline.